THE EFFECT OF NUTRITIONAL EDUCATION THROUGH PUZZLE GAMES TO CHILDREN'S PERCEPTION ABOUT SNACKS SELECTION IN SD PESAWAHAN SIDOARJO SCHOOL - siti indatul laili; Siti Mariyah Ningsih (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
Stages of school-age children have more activity outside the home; this causes children often forget the time to eat,so they buy snacks to delay hunger. By providing balanced nutrition education through puzzle games can change the perception of children so they can choose a healthy snack. The purpose of this research is to prove the influence of balanced nutrition education through puzzle game to children's perception about the selection of snacks in SD PesawahanSidoarjo. This research design uses one group pre-post test design. The population of this study is all 4-6 grade children in SD PesawahanSidoarjo with 54 respondents. The sample of this research is some of grade 4-5 students in SD PesawahanSidoarjo as many as 48 respondents taken with simple random sampling. Measuring tool used a questionnaire to assess perception with 100% valid and reliable test with Ï = 0.961. Time of study March 2017. A statistic test using T-Test. The results showed that respondents who had a positive perception of 25 (52.1%) of respondents increased to 36 (75%) respondents after balanced nutrition education through puzzle game. T-test result Ïcount 0.000 = and atable = 0,05. This means balanced nutrition education through puzzle games can improve the perception of children about the selection of snacks in SD PesawahanSidoarjo. Learning through puzzle games can foster self-confidence in children and children able to solve problems. This makes the child more comfortable so that the message conveyed through the puzzle game will be easily understood by the child. This increased understanding will affect the perception of the child.